(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper examines the evolution of economic thought, a necessary task to explain its present situation, which is the conclusion of the article. It begins with Adam Smith and the classics´ doctrine, which Karl Marx roughly rejects. The neoclassics introduce new instruments, which are still used today, but can´t explain the Great Depression until Keynes´ arrival. The Neoclassical synthesis joins both theories, but it is criticised by monetarists and neokeynesians, who will give birth to the two current schools, the new classic economy and the new keynesian economy.